Catalyst@Metal Hybrids in a One‐Pot Multistep Opposing Oxidation and Reduction Reaction Sequence. Issue 5 (18th January 2017) - Shapiro, Leora; Avnir, David
Abstract: We report the feasibility of the catalysis of contrasting reactions, oxidation and reduction, in a multistep process that also involves a condensation reaction all performed with hybrids of catalytic organometallic complexes entrapped within metals ([complex]@metal). Two routes were explored for the multistep process. The first route used a combination of an oxidizing Ir complex entrapped in Ag ([Ir]@Ag) and a reducing Rh complex entrapped in Ag ([Rh]@Ag). The second route used a single composite material, namely, [Ir]@Pd, in which [Ir] acted as the oxidizing catalyst, and Pd was the reducing catalyst. Both routes were efficient for the heterogeneous catalytic oxidation and reduction reaction sequence. Towards the goal of a one‐pot multistep oxidation and reduction process, a detailed study of the catalytic alcohol oxidation properties of the heterogeneous [Ir]@Ag and [Ir]@Pd was performed. As the arsenal of available hydrogenation catalysts exceeds by far that of oxidations, this part of the study is, we believe, of general interest in itself, as a new alternative to heterogeneous oxidative catalysis. Abstract : All in one : We report the feasibility of the catalysis of contrasting reactions, oxidation and reduction, in a multistep process that also involves a condensation reaction, all performed with hybrids of catalytic organometallic complexes entrapped within metals ([complex]@metal). Two routes are explored for the multistep process: the combination of an oxidizing Ir complex entrapped in Ag ([Ir]@Ag) and a reducing Rh complex entrapped in Ag ([Rh]@Ag), and [Ir]@Pd, in which [Ir] acts as the oxidizing catalyst, and the Pd was the reducing catalyst.